THE IMPORTANCE OF DIAGNOSTICS OF THE SPORTSMENS BIOCHEMICAL STATUS - Franja Fratrić; Nenad Sudarov (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Widespread opinion that all the sportsmen nowadays "are sick", as well as the results of the analysis of the random sample from all over Europe, show that very few of them are not under some kind of treatment or doctor's supervision. This should be a warning for experts and scientists in sports, for making a strategy to prevent this trend. Sickness is a huge individual and socio-economical problem. Sportsmen nowadays are under extreme pressure, without control of biochemical processes. There is a risk of becoming an "organism dump" full of wasteful and harmful substances, that are sediment. These are: - acids - medicaments - chemicals - proteins, etc. The cause of an error is possible resolve only by knowing its origin. This is precisely the most important function of the diagnostics in sport. In this paper we are presenting the strategy of the diagnostics of the biochemical status of the sportsman's organism. Moreover, we are bringing out the key problems and suggesting concrete prevention measures.